2018
DOI: 10.1007/s00774-018-0933-0
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin and parathyroid hormone responses to acute whole-body vibration and resistance exercise in young women

Abstract: Whole-body vibration (WBV) has been shown to improve bone mineral density, and muscle strength and power. No studies to date have examined sclerostin and parathyroid hormone (PTH) responses to WBV combined with resistance exercise (RE). This randomized crossover study compared acute serum sclerostin and PTH responses to RE and WBV + RE in young women (n = 9) taking oral contraceptives. Participants were exposed to 5 1-min bouts of vibration (20 Hz, 3.38 peak-peak displacement, separated by 1 min of rest) befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Moreover Falk et al, (21) reported mixed results that PTH levels were same in male adolescents and adult; at rest and during experiment, increasing considerably 5 minutes after activity, decreasing after 60 minutes post-exercise, and returning to resting values within 24 hours . The current study's findings were reinforced by Sharma-Ghimire et al, (22) who discovered that in young women, there was no transient increase in PTH in response to transient whole-body vibration and resistive training, but it did exhibit a significant drop after 30 minutes for both treatments. The mechanisms of PTH exercise reactivity are not really recognized, according to their study; which showed that the amount of PTH produced in response to acute physical stimuli varies based on the kind of exercise .…”
Section: Discussionsupporting
confidence: 66%
“…Moreover Falk et al, (21) reported mixed results that PTH levels were same in male adolescents and adult; at rest and during experiment, increasing considerably 5 minutes after activity, decreasing after 60 minutes post-exercise, and returning to resting values within 24 hours . The current study's findings were reinforced by Sharma-Ghimire et al, (22) who discovered that in young women, there was no transient increase in PTH in response to transient whole-body vibration and resistive training, but it did exhibit a significant drop after 30 minutes for both treatments. The mechanisms of PTH exercise reactivity are not really recognized, according to their study; which showed that the amount of PTH produced in response to acute physical stimuli varies based on the kind of exercise .…”
Section: Discussionsupporting
confidence: 66%
“…A transient increase in serum sclerostin has been reported following an acute bout of WBV [22], combined resistance training with WBV [23], physical activity [18,19], high-intensity interval exercise [20], and jumping [21]. One study found a lack of change in sclerostin immediately following five 1-minute bouts of WBV (20 Hz, 3.38 mm, ~2.7 g) [23], whereas another study reported a 91 % increase in plasma sclerostin from pre-to 10 minutes post-WBV (40 Hz, 2 mm, ~2.7 g) [22]. The contrast in findings may be attributed to the differences in the time point analyses or factors relating to the vibration stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…One potentially important mechanism by which mechanical stimuli influence osteocyte activity is through regulating sclerostin, an osteocyte-derived secreted glycoprotein, which inhibits bone formation through inhibition of the Wnt/β-catenin pathway [16,17]. There have been few human studies to date reporting the response of sclerostin to acute exercise, although current evidence suggests that sclerostin levels increase following an acute bout of physical activity [18,19], high-intensity interval exercise [20], jumping [21], whole-body vibration (WBV) [22], and combined high-intensity resistance training and WBV [23].…”
Section: Acute Response Of Sclerostin To Whole-body Vibration With Blood Flow Restrictionmentioning
confidence: 99%
“…Császárné Gombos et al shown that serum sclerostin concentrations increased in participants in the resistance exercise group and walking group compared to its base level [29]. Additionally, the study of Falk et al, in which blood samples were taken after plyometric exercises and the study of Sharma-Ghimire et al, in young women researched response to the whole-body vibration and high intensity resistance exercise also came to the conclusion that sclerostin concentrations increased after acute exercise [30,31]. When considering studies depicting acute exercise one must notice that those studies most often don't include long term variability.…”
Section: Influence Of Physical Activity On Sclerostin Level In Blood mentioning
confidence: 99%